Autoclave Testing a High-Arsenic, High-Carbonate Gold Ore at the Getchell Mine, Nevada - D. Tahija (The Minerals, Metals and Materials Society, 1999)
The Getchell Mine produces gold from a geologically complex ore bearing high concentrations of arsenic and carbonate minerals. The mill treats the ore using high temperature aqueous oxidation in autoclaves, followed by conventional carbon-in-leach gold recovery. We laboratory tested a variety of Getchell ores to determine the effects on gold recovery of conventional factors such as grind size and retention time, as well as the influence of factors such as ore variability and preliminary carbonate destruction. Because the mill is currently operating, we were able to directly compare certain laboratory predictions with operational results.